Applying Digital Storytelling to Improve Students’ Writing Narrative Text Learning - Goestina Goestina; Kiki Rezky Mayasari; Silfa Nugrawati (BATARA DIDI : English Language Journal, 2022)
Based on a preliminary investigation into the reasons of pupils' failure to write narrative texts. This study seeks to explain the ambiance of enhancing students' story writing skills via the use of Digital Storytelling. Together, the collaborator and I created the lesson plans, implemented the activities, made observations, and reflected on the outcomes. To accomplish these aims, we performed two cycles of action research consisting of planning, implementation, observation, and reflection. Using classroom observation, interviews, questionnaires, and assessments, the data was obtained. Digital Storytelling was beneficial in enhancing students' story writing skills, according to the data. This is evident from the results of three tests: the pre-test, the test after cycle 1 and the test after cycle 2. Where the typical test score is 3.57 on the first test, 5.36 on the second, and 7.01 on the third. It is also evident from the results of the survey, in which 52 percent of students agree and 36 percent of students strongly agree and provide positive comments, while the remaining students provide negative responses. The interview findings also revealed the teacher's optimism and positive reactions.